Schöpferische Erfahrungen von Grundschulkindern und Studierenden beim Schreiben Eine phänomenologische Studie - Herrmann, Franziska (Lernen und Studieren in Lernwerkstätten. Impulse für Theorie und Praxis, 2023)
The study describes creative experiences as learning experiences of students and primary school children in the context of the Learning and Research Workshop Primary School of the TU Dresden (LuFo). The aim is to elaborate what is 'special' about learning in university learning workshops in order to contribute to the current discourse on the self-understanding of university learning workshops. The study emerged from the TUD-Sylber project Teaching, Learning and Research in Workshops, in which workshop seminars in the format of research-based learning in the LuFo were developed from 2016 to 2019 under the direction of Prof. Dr. Jeanette Hoffmann. The seminar I developed, Didactic Research Workshop on Creative Writing, forms the framework for the empirical study. The central research question is: How does learning take place in university learning workshops? The starting point is the phenomenological understanding of learning as experience in connection with creative processes. This is examined in three objects: in writing processes of primary school children, in free children's texts as well as in reflection conversations with students.